Income generation in informal sector: A case study of the street vendors of Kathmandu Metropolitan City - Adhikari, Dipak Bahadur (Economic Journal of Development Issues, 2012)
Street vending is important to income earn and poverty alleviation for some people of Nepal. The street trade provides employment and income generation for the rural poor in the urban areas. And not only rural poor are getting earning opportunities in the informal economy; this has been providing goods in cheaper price to urban poor. This paper analyzes the determinants of the street vender’s income. It examines whether the income from vendor business of the people doing street business in Kathmandu metropolitan city increases with the rate of increase in investment, education and labor supply. DOI: http://dx.doi.org/10.3126/ejdi.v13i0.7193 Economic Journal of Development Issues Vol.13 & 14 2011, pp.1-14